Green Public Service Innovation: Integrating Environmental Values into Local Government Service Delivery - Yasmeardi, F.; Rizke, Dian; Kosassy, Siti Mutia; J., Syamsu; Marwandizal, Marwandizal (PT Mattawang Mediatama Solution, 2025)
This study explores the integration of environmental values into public service innovation commonly referred to as green public service innovation within the context of local government service delivery in Padang, West Sumatra. Amid escalating environmental challenges and the urgency of achieving Sustainable Development Goals (SDGs), local governments are increasingly expected to move beyond efficiency and adopt eco-conscious service models. This research employs a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine five key variables: organizational commitment, organizational culture, community participation, green leadership, and green public service innovation. The findings reveal that organizational commitment, organizational culture, and community participation all have significant direct impacts on green public service innovation. Furthermore, green leadership not only directly influences innovation but also plays a moderating role by strengthening the effect of organizational commitment on innovation outcomes. The results emphasize that green innovation in the public sector requires more than technology adoption it demands aligned leadership, an enabling institutional culture, and active community involvement. In Padang’s case, local wisdom and environmental awareness present opportunities for designing inclusive and contextualized green innovations. Strong leadership that embeds environmental values into strategic planning and operational systems significantly enhances institutional resilience and citizen trust. The research contributes to public administration literature by offering empirical support for the systemic relationships between organizational factors and sustainable service delivery. It also provides actionable insights for local governments seeking to institutionalize environmental values in public services.